Vegetation Structure, Composition, and Soil Properties of Dry Land on Islands in Balikpapan Bay, East Kalimantan - Sayektiningsih, Tri; Sitepu, Bina Swasta; Yassir, Ishak; Sari, Ulfah Karmila; Mukhlisi, Mukhlisi; Ma'ruf, Amir (Jurnal Biodjati, 2020)
Some small islands in Balikpapan Bay consist of dry land which may have different vegetation structure and composition. Our study was the first to uncover vegetation conditions and soil proper-ties of dry land on small islands in Balikpapan Bay, which has never been conducted before. The research was carried out on Kalawasan and Karantina islands. Information on vegetation was obtained by applying a line transect method. Data on soil properties were col-lected by setting up 3 sampling plots in each transect of vegetation. Parameters used for analysing vegetation including relative densi-ty, relative frequency, relative dominance, Shannon-Wiener diversi-ty index, evenness index, and similarity index. Meanwhile, data on soils were analysed descriptively. Trees on Kalawasan island were comprised of 241 individuals belonging to 21 species. There were 61 individuals (22 species) of trees on Karantina island. The diver-sity index of trees on Kalawasan and Karantina island was 2.55 and 2.72, respectively. The tree evenness index was 0.84 on Kalawasan island and 0.88 on Karantina island. The index of similarity for trees between the two islands was 0.21. Furthermore, the soil character-istics on Kalawasan and Karantina islands showed similarities. In general, soil in Kalawasan and Karantina islands could be catego-rised as marginal soil which was common in East Kalimantan. Con-sidering the rapid loss of tropical forests in the mainland of Kali-mantan indicates that the small islands of Balikpapan Bay play an important role in future biodiversity conservation in East Kalimantan.